Empathy as Mediator in Relationship between Self-Compassion and Prosocial Behavior among Adolescents - Asri Widyastuti; Luh Surini Yulia Savitri (Faculty of Psychology, Universitas Gadjah Mada, 2023)
As a construct which promotes having compassion for ourselves, self-compassion has been found to have an inconsistent relationship with prosocial behaviour. However, the relationship between self-compassion and prosocial behaviour might be mediated by another predictor, such as empathy. The lack of literature discussing self-compassion in adolescents also encouraged this research. In this study, we examine the mechanism between self-compassion and prosocial behaviour through empathy as a possible mediating factor. Participants of this study were 303 adolescents in Indonesia aged 11-18 years old who filled out Self-Compassion Scale, Basic Empathy Scale and Prosocial Tendencies Measure-Revised. All the data were analyzed using the mediation analysis using approach introduced by Hayes. The results of statistical analysis showed there was a direct significant effect of self-compassionon prosocial behaviour (c = 0.10, p<0.05), and there was no significant effect from self-compassionon empathy (b=0.04, 95% CI [-0.030, 0.101]). Therefore, there was no indirect effect from self-compassionto prosocial behaviour through empathy. It can be concluded that empathy is not a mediator in the relationship between self-compassion and prosocial behaviour in adolescents.